Circadian Oscillations within the Hippocampus Support Memory Formation and Persistence - Eckel-Mahan, Kristin L. (Frontiers in Molecular Neuroscience, 2012)
The ability to sustain memories over long periods of time, sometimes even a lifetime, is one of the most remarkable properties of the brain. Much knowledge has been gained over the past few decades regarding the molecular correlates of memory formation. Once a memory is forged, however, the molecular events that provide permanence are as of yet unclear. Studies in multiple organisms have revealed that circadian rhythmicity is important for the formation, stability, and recall of memories (Gerstner et al., 2009).The neuronal events that provide this link need to be explored further. This article will discuss the findings related to the circadian regulation of memory-dependent processes in the hippocampus. Specifically, the circadian-controlled mitogen-activated protein kinase (MAPK) and cAMP signal transduction pathway plays critical roles in the consolidation of hippocampus-dependent memory. A series of studies have revealed the circadian oscillation of this pathway within the hippocampus, an activity that is absent in memory-deficient, transgenic mice lacking Ca2+-stimulated adenylyl cyclases. Interference with these oscillations proceeding the cellular memory consolidation period impairs the persistence of hippocampus-dependent memory. These data suggest that the persistence of long-term memories may depend upon reactivation of this signal transduction pathway in the hippocampus during the circadian cycle. New data reveals the dependence of hippocampal oscillation in MAPK activity on the suprachiasmatic nucleus, again underscoring the importance of this region in maintaining the circadian physiology of memory. Finally, the downstream ramification of these oscillations in terms of gene expression and epigenetics should be considered, as emerging evidence is pointing strongly to a circadian link between epigenetics and long-term synaptic plasticity.